Almost president : the men who lost the race but changed the nation - Farris, Scott (Guilford, Conn. : Lyons Press, 2012)
Profiles 12 men who have run for the presidency and lost, but who, even in defeat, have had a greater impact on American history than many of those who have served as president. An appendix provides briefer profiles on an additional 22 candidates.
The concession -- Henry Clay, 1824, 1832, 1844 -- Stephen Douglas, 1860 -- William Jennings Bryan, 1896, 1900, 1908 -- Al Smith, 1928 -- Thomas E. Dewey, 1944, 1948 -- Adlai Stevenson, 1952, 1956 -- Barry Goldwater, 1964 -- George McGovern, 1972 -- Ross Perot, 1992, 1996 -- Al Gore, John Kerry, and John McCain, 2000, 2004, 2008.
Includes bibliographical references (pages 323-333) and index.
Keywords: Presidential candidates -- United States -- Biography; Presidents -- United States -- Election -- History; United States -- Politics and government; Politics and government; Presidential candidates; Presidents -- Election; United States; Biographies; History; Nonfiction; Biographies